COMPARISON IS PRESENTED BETWEEN ENDURANCE AND POWER TESTS AND MEASUREMENTS FOR PJOK TEACHERS IN SEKADAU - Ade Rahmat; Ryandhika Kurniawan; Nuri Utami; Gusti Setiawan; Sutantio (IKIP PGRI Pontianak, 2024)
In this study, the assessment of endurance and power is of paramount importance in order to enhance the efficacy of training regimens. The objective of this study is to determine whether there is a comparison between tests and measurements of endurance and power. The objective of this study is to ascertain the outcomes of the comparison between tests and measurements of endurance and power. The results of the aforementioned test are as follows. In the beep test, 0% of men and 0% of women did not meet the 100% criterion. In the plank test, all participants failed to meet the criterion. In the medicine ball test, 0% of males did not fit 100%, 80% of females did not fit 20%, and in the vertical jump, 66.67% of males did not fit 33.33%, while 100% of females did not fit 0%. The results of this study are expected to enhance the quality of PJOK learning, foster the development of athletes, and elevate the competitiveness of achievements between schools in Sekadau Regency. The implementation of this test in a systematic and sustainable manner can yield significant benefits for PJOK learning and student achievement. It is imperative that this program be implemented on an ongoing basis and that cooperation be sought from a variety of parties.